2003
DOI: 10.1038/sj.ijir.3901021
|View full text |Cite
|
Sign up to set email alerts
|

Acupuncture in the treatment of psychogenic erectile dysfunction: first results of a prospective randomized placebo-controlled study

Abstract: In a prospective study, we investigated the potentially curative effect of acupuncture in patients with psychogenic erectile dysfunction (pED). A total of 22 patients with pED were randomized into two groups. They were either treated with acupunture specific against ED (treatment group) or acupuncture specific against headache (placebo group). Nonresponders of the placebo group were crossed over to the treatment group. Prior to acupuncture, serum sexual hormone levels, IIEF score, nocturnal penile tumescence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(54 citation statements)
references
References 19 publications
(32 reference statements)
0
52
0
Order By: Relevance
“…Accordingly, 108 identified reports 7–114qualified for review and analysis.They encompass a wide range of condi‐tions/symptoms, including: osteoarthritis/knee pain, migraine, low back pain, pelvic pain, hot flashes, labor pain and labor initiation, analgesic and sedative ef‐fects in surgery/cancer pain, tension‐type headache, shoulder/arm pain, embryo transfer, irritable bowel syndrome, allergic rhinitis, depression, fibromyalgia, myofascial pain, insomnia, inflammatory breast in lactating women, stroke reha‐bilitation, anxiety, nausea and vomiting, dry eyes, hypertension, post‐traumatic stress disorder (PTSD), recurrent cystitis, psychogenic erectile dysfunction, chronic post‐stroke leg spasticity, overactive bladder, refractory heartburn, rheuma‐toid arthritis, disabling breathlessness, impingement syndrome, cervical spondy‐losis, chronic obstructive pulmonary disease (COPD), diabetic bladder dysfunc‐tion, balance function after stoke. The sample size of those articles varied from 16 to over 3000.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, 108 identified reports 7–114qualified for review and analysis.They encompass a wide range of condi‐tions/symptoms, including: osteoarthritis/knee pain, migraine, low back pain, pelvic pain, hot flashes, labor pain and labor initiation, analgesic and sedative ef‐fects in surgery/cancer pain, tension‐type headache, shoulder/arm pain, embryo transfer, irritable bowel syndrome, allergic rhinitis, depression, fibromyalgia, myofascial pain, insomnia, inflammatory breast in lactating women, stroke reha‐bilitation, anxiety, nausea and vomiting, dry eyes, hypertension, post‐traumatic stress disorder (PTSD), recurrent cystitis, psychogenic erectile dysfunction, chronic post‐stroke leg spasticity, overactive bladder, refractory heartburn, rheuma‐toid arthritis, disabling breathlessness, impingement syndrome, cervical spondy‐losis, chronic obstructive pulmonary disease (COPD), diabetic bladder dysfunc‐tion, balance function after stoke. The sample size of those articles varied from 16 to over 3000.…”
Section: Resultsmentioning
confidence: 99%
“…Engelhardt et al (63) reported another randomized placebo-controlled trial among 21 patients with psychogenic ED. Acupoints that are conventionally used to treat headache were applied in the control group.…”
Section: Role Of Acupuncture In Male Subfertilitymentioning
confidence: 98%
“…Acupuncture involves stimulation of the body's energy flow channels with unassisted or assisted (e.g., by electric currents) needling of organ and functionspecific acupuncture points, which redirect and restore the natural balance of blocked systems. This may involve activation of corresponding neuroendocrine-, vasoactive-, and immune-modulators, 11 all of which play a role in female sexual physiology. 3 Several studies have demonstrated the efficacy of acupuncture for treating various symptoms that are common to postmenopausal women.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective, crossover, randomized, controlled pilot study 11 examined acupuncture specific to ED as an intervention versus acupuncture targeted at headache (control) in patients with psychogenic ED (pED). Of the 20 subjects who completed the study, more than one third responded to the intervention acupuncture as measured by pre-and post-trial criteria, which included serum sex-hormone levels and erectile response.…”
Section: Introductionmentioning
confidence: 99%